Impact Of Maternal Deprivation on Adolescents’ Psychosocial Development in the Buea Municipality, South West Region of Cameroon - Bongwong Bruno; Nyambia Adrien (International Journal of Educational Excellence and Innovation, 2024)
The impact of maternal deprivation on adolescents’ psychosocial development in the Buea municipality, South West region. The objectives of this study were: to find out how maternal divorce influences on the psychosocial development of adolescents, to investigate how maternal death influenced the psychosocial development of adolescents and to identify the influence of maternal illness on the psychosocial development of adolescents. This study made use of the survey research design and the simple random sampling technique was used to select a sample of 50 students for the study. The questionnaire was used for data collection. Data was analyzed using the percentage and thematically. The findings revealed that 72% of the respondents supported the fact that when the mother is divorced it brings about indiscipline, truancy, promiscuity and aggressiveness, 62% of the respondents supported that maternal death brought about promiscuity, truancy and waywardness in adolescents and 62% of the respondents supported that maternal illness brought about negative impacts on the psychosocial development of adolescents. The study recommended that childcare activists and practitioners work towards creating a society where adolescents are very involved and not just mere victims of circumstances beyond their control and to find good therapeutic interventions to assist adolescents who are have been deprived from maternal care.